Citra Sekolah dan Promosi Terhadap Keputusan Siswa dalam Memilih Sekolah Pada SMAN 1 Kerambitan Tabanan - Dicky Mahendra, Kadek Agus; Wimba, I Gusti Ayu; Sunny, Milla Permata (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
In a business or company, it's really important to pay attention to the decisions students make, because their decisions are key to reaching the industry's goals. Students make choices based on things like how the school is seen and advertised. This study wants to find out how the school's reputation and how it advertises itself affect the choices students make when picking a school at SMA Negeri 1 Kerambitan. The way they study is by using numbers and statistics. This study was done at SMA Negeri 1 Kerambitan. 137 people were used in the study. This research shows that the way a school is seen has a big impact on students' choices. The tcount is 7. 257 and the significance figure is 0. 000, which means this has been proven. Also, advertising has a big impact on students' choices, supported by the tcount of 5. 239 and a significance figure of 0. 000 Finally, both the school's image and advertising have a positive and important impact on students' decisions, as shown by the F count of 86. 194 and a significance number of 0. 000 The independent variable has a big effect on student decisions, about 55. 6% This study suggests that SMA Negeri 1 Kerambitan should regularly improve its learning facilities, school buildings, and infrastructure. It also recommends doing more promotions and making sure the students graduate with good skills.